The Angel of History: Walter Benjamin and Theodor W. Adorno - Schwarz Langer, Margarita (Estudios de Filosofía, 2004)
This paper intends to establish a small correlation, by way of hemage, between Theodor W. Adorno's though; and that of his beloved teacher, Walter Benjamin. He tries that bind both thinkers can be found in the weight of the words that they share, in the context of German critical philosophy and the Jewish roots that links them. Under the allegoric figure of the angel of history, bonds are woven among a selection of quotations taken from Adorno's Negative Díalectics and front some concepts expounded in Benjamin's The Original of Baroque Drama.